Vedānta and Bhagavadgītā: the unpublished writings of K. Satchidananda Murty - Murty, K. Satchidananda (Routledge, 2024)
Some thoughts on the Veda and its study -- The Vedāntic vision -- Reason in Vedānta -- The Advaitic vision -- Śaṅkara's conception of God : effects of superimposition -- Śri Śaṅkarācārya : some observations -- Śaṅkara's views on religious life -- Gītā Bhāṣyatraya Vivecana : reflections on the three Bhashyas of the Gītā -- 'Here' (Iha) and 'There' (Āmutra) : 'The excellent' (Śreya) and 'The pleasant' (Preya).